The rise of Protestant evangelism in Ecuador, 1895-1990 - Goffin, Alvin M. (Alvin Matthew) (Gainesville : University Press of Florida, 1994)
"Review of Protestantism in Ecuador. Provides historical account of religious activities. Documents struggle of Protestant denominations to gain recognition from the Catholic Church and acceptance by indigenous communities"--Handbook of Latin American Studies, v. 57.
Includes bibliographical references (p. 171-183) and index.
Keywords: World Radio Missionary Fellowship; Summer Institute of Linguistics; World Vision International; Missions, American -- Ecuador; Evangelistic work -- Ecuador; Protestant churches -- Ecuador; Ecuador -- Church history -- 19th century; Ecuador -- Church history -- 20th century